Antonio Latini's "the modern steward, or the art of preparing banquets well" : a complete English translation - Latini, Antonio (Foundations, 2019)
"Latini's masterpiece of Baroque cooking and household management was the first book to publish recipes using tomatoes and chilli peppers. This first complete English translation presents the text with contextual introduction and notes to aid the reader's understanding. The Modern Steward was published in Naples in 1692-94, when the city was a major cultural centre. It includes a wealth of recipes, plus discussions of the kitchen and serving staff, setting the table, menus, protocol, entertainment, and wines. There are also sections on health, accounts of specific banquets, and even a description of an eruption of Vesuvius. It is the last great book of the Italian Renaissance and Baroque cooking tradition. Latini was also interested in local ingredients and customs, and open to new French trends. The book will interest historians of early modern Italy, food, material culture, and the social and cultural life of the European elites, as well as connoisseurs of fine dining, and cooks."--